PENGEMBANGAN BAHAN AJAR MATEMATIKA PADA MATERI PROGRAM LINEAR DENGAN MODEL PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA - Hilda Rahmawati, Ajeng Ajeng; Marlina, Rani; Nurjanah, Nurjanah; Hakim, Luki Luqmanul; Marwan, Silmi Aulia; Wahyuni, Nurhopipah; Kosasih, Usep (Uninus Journal of Mathematics Education and Science (UJMES), 2023)
This research supported by the lack of student’s mathematical understanding ability, and the need for the development of linear programming material for students.The purposes of this research are: to  describe the  characteristics of linear programming material written with problem-based learning model, and assess  the quality of material considered from validity, practicality, and effectiveness.The research used quantitative  and qualitative approaches, with research and development method, in form of Dick and Carey’s design. Research was conducted at one of senior high school in Bandung. The instruments used are: validation’s sheets, the mathematical understanding test, observation sheets, and questionnaire. According to the data processing and analysis of the development of material, researcher have two conclusions. The first conclusion, characteristic of material developed was:  based on the curriculum 2013 standard with a KI-1 not specified in teaching materials and some KI-2 not all included in material, the presentation of material developed according to a problem-based learning model, and equipped with a problem, examples, exercise about, and evaluate compiled based on an indicator of mathematical understanding ability. The second conclusions, instruction materials developed was valid, practical, and effective.